Research in accounting in emerging economies. Vol. 10 - Uddin, Shahzad; Tsamenyi, Mathew (Emerald, 2010)
Accounting research in emerging economies has been growing significantly over the last two decades due to the increasing recognition of the roles that accounting systems play in these environments. Globalization of capital markets and competition; the emergence of international accounting standards and structural adjustment programmes have all brought accounting issues in emerging economies to the fore. Research papers in the current volume have highlighted the implications of the aforementioned issues. The papers have examined various issues including the adoption of International Financial Reporting Standards (IFRS) and International Public Sector Accounting Standards (IPSASs), management accounting change in the context of public sector reforms, corporate reporting disclosures, auditing, etc. The papers published in this volume have provided us the opportunities to further engage with wide ranging empirical and theoretical issues that will have policy implications and also generate future academic debates. Overall, the volume advances debate on the role of accounting reforms in areas such as accounting standards, disclosures, and corporate governance in both the public and private sectors in emerging economies. We believe the audience will find the papers interesting and insightful in terms of theoretical development, practices, policy implications and future research directions.
Keywords: Accounting -- Developing countries.; elektronické knihy; electronic books